Pusat Konservasi Penangkaran Penyu di Pulau Derawan Kabupaten Berau Kalimantan Timur - Desta Ria, Ardyana; Alimuddin, Aris; Budy, Andas (Universitas Muslim Indonesia, 2025)
Derawan Island is one of the islands that has an interesting habitat for turtles to carry out egg-laying activities. This island is included in the Regional Government of Berau Regency, East Kalimantan which is famous as the largest green turtle spawning area in Indonesia. Of the six types of turtles spread in the waters in Indonesia, there are three types of turtles on Derawan Island, including green turtles, hawksbill turtles, and leatherback turtles. Due to the increase in illegal capture and collection of turtle eggs in the Derawan Islands, the number of biota has decreased. The development activities in coastal areas that can damage turtle habitats to lay eggs such as the construction of beach tourism facilities and the construction of coastal walls or embankments. The current turtle breeding buildings in general are very inadequate. Therefore, based on the explanation above, in line with the efforts to manage turtles in Indonesia, a forum is needed for turtle management actors in the field. With the existence of a turtle breeding conservation center to manage turtle eggs that will hatch and also as a place to protect turtles that are in the process of breeding, it is hoped that it can protect the declining turtle population